Bezpieczeństwo jako wartość prawnie chroniona - Karpiuk, Mirosław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2019)
One of the basic, legally protected values is safety. Due to its nature, an employer provided protection not only by means of laws and regulations, but also by the Constitution of the Republic of Poland and as such the safety took on a new dimension. In the personal aspect – civil safety is protected, in the institutional aspect – the safety of the country, in the substantive aspect – public, economic, social safety etc. From the point of view of the safety and its importance for the society and the country, the protection of this value is allowed at the expense of the freedom, human and citizen rights. Such interference in the constitutional freedoms cannot however infringe their essence and it is allowed only if the safety cannot be provided by other means, but at the same time it cannot be excessive. The legislator clearly provides that any limitation upon the exercise of constitutional freedoms and rights may be imposed only by law, and only when necessary in a democratic state for the protection of the state and public order or for the protection of the natural environment, health and public morals or for the protection of freedoms and rights of other people. Similarly to ensuring enforcement regulations, safety is one of the most important premises for their implementation. The municipal council may pass enforcement regulations within a scope not otherwise regulated in acts or other regulations commonly applicable regulations if such is necessary for the protection of human life or health and to assure public order, peace and security. Similar legal measures are meant for the voivodship and poviat. The municipal council may pass enforcement regulations within a scope not otherwise regulated in acts or other regulations commonly applicable regulations, in duly justified cases, provided that the reasons occur within the area of more than one municipality. The voivode can pass enforcement regulations within a scope not otherwise regulated in acts or other regulations commonly applicable if such is necessary for the protection of human life or health and to assure public order, peace and security. Enforcement regulations cannot be passed by a province government.